ENTREPRENEURSHIP EDUCATION AND TRAINING PROGRAMS IN DENMARK: KEY FACTORS - T. A. VOLOSHINA (Высшее образование в России)
The article presents the experience of entrepreneurship education in Denmark at all levels of education, the system of gradual inclusion of young generation in entrepreneurial activity. An analysis of the Strategy for education and training in entrepreneurship adopted by of the Government of Denmark is given, which is the basis for training of young people competent in entrepreneurship. Entrepreneurial education in Denmark is provided by the innovation program “Denmark – A Nation of Solutions”, which touches upon all the levels of education. The Danish Enterprise Fund (FFE-YE) is in charge for the realization of the program. The article reveals the main directions of work organized by FFE-YE: the creation of a single system of entrepreneurial training; development of training programs for trainers and managers for entrepreneurship training; establishment of a network, contacts and close cooperation between industry and educational institutions. FFE-YE has worked out the system of extracurricular activities, which allow motivating young people to develop entrepreneurship, such as business camps, forums, festivals, fairs. The paper pays special attention to the peculiarities of teacher training in the format of educational innovation and entrepreneurship. Summarizing the Danish experience in the sphere of entrepreneurial education the author marks out the key factors that encourage the development of students’ entrepreneurial skills and promotion of their business ideas.